Towards the Implementation of the Environmental and Economic Doctrine of Energy Sector Development: An Environmental and Economic Assessment of Public-private Partnerships in Decarbonization - Shakharova, Aliya; Alamanova, Chinara; Olshanska, Oleksandra; Kafka, Sofiia; Tuts, Ilona; Dugalova, Gulnar (International Journal of Energy Economics and Policy, 2023)
The disruption of the energy system at the global and local levels requires an intensification of public policy in this area to respond quickly to changes. Strategic planning and public policy changes are needed to ensure the sustainability of the energy sector. In the short term, Ukraine's priority should be improving energy security. Natural gas will be essential in balancing electricity on the road to decarbonization. The transition to renewable energy sources can achieve natural gas self-sufficiency. The article analyzes the directions of energy security and normative and legal regulation in the energy sector. It is established that the main direction of transition to decarbonization in an unstable external environment is public-private partnership mechanisms. The introduction of this mechanism provides benefits for all interested parties. In order to choose the most effective form of public-private partnership, a flowchart of analysis and evaluation of environmental and economic efficiency was developed. This flowchart applies to decarbonization projects and considers regional features of the energy sector and differences in readiness for the transition to the decarbonization of different countries. Limitations of the model application are the imperfect regulatory framework and the high instability of the external environment. The main objective is to simplify the procedures for attracting investment in the energy sector and reduce the time for project preparation and submission, which will help to implement the most effective projects in the short term and make the transition to decarbonization in the long term.